Optimal Lower Generalized Logarithmic Mean Bound for the Seiffert Mean. (24th March 2013) - Song, Ying-Qing; Qian, Wei-Mao; Jiang, Yun-Liang; Chu, Yu-Ming
Abstract : We present the greatest value p such that the inequality P ( a, b ) > L p ( a, b ) holds for all a, b > 0 with a ≠ b, where P ( a, b ) and L p ( a, b ) denote the Seiffert and p th generalized logarithmic means of a and b, respectively.